QUALITY CONTROLLING IN THE FUNCTION OF SURVIVAL AND DEVELOPMENT OF A COMPANY - Vukašinović, Marija; Vukašinović Јovan; Obradović, Saša (Economics of Agriculture, 2010)
Controlling as one of the means of quality management is a recent trend. Thus, we dealt with key elements and terms related to controlling in this paper. We also discussed the reasons for implementation of this management quality technique, the present state and development in the future.